Direito penal e pós-modernidade: bases humanistas e conteúdo ético - Busnello, Priscila de Castro (2012)
The global society is a reality. At the same time that the mankind experiences the dynamism of the big and uninterrupted (macro)transformations, it was not possible to comprehend and enforce, thoroughly, the fundamental rights of the human being as a unique and singular person. Due to those findings, this study has as main objective to understand post-modernity, recognizing its importance, without forgetting to preserve human rights and human dignity, to establish the minimal humanistic bases for the model of a new society. Aim to reach the goals, a compiling method utilized, with the association of different subjects in a way to presents a summarize panorama on several perspectives on the update changing on the readings of humanity. But, with the development of the presented ideas, the scientific methodology takes the place in directing development of the investigation searching coherent proposals to a conciliation between the inevitable global integration and the effective preservation of the dignity of the human being. The results concerning law indicate the need to overcome the old fashion debates with are just formal and superficial, with un updating of the comprehension on the role of the criminal law in post-modernity. It should, more than ever, helping strengthen the ethical conduct and the commitment of the human being with their peers